Sex differences in the response of the alveolar macrophage proteome to treatment with exogenous surfactant protein-A - Phelps, David S (BioMed Central, 2012)
BACKGROUND: Male wild type (WT) C57BL/6 mice are less capable of clearing bacteria and surviving from bacterial pneumonia than females. However, if an oxidative stress (acute ozone exposure) occurs before infection, the advantage shifts to males who then survive at higher rates than females. We have previously demonstrated that survival in surfactant protein-A (SP-A) knockout (KO) mice compared to WT was significantly reduced. Because the alveolar macrophage (AM) is pivotal in host defense we hypothesized that SP-A and circulating sex hormones are responsible for these sex differences. We used 2D-DIGE to examine the relationship of sex and SP-A on the AM proteome. The role of SP-A was investigated by treating SP-A KO mice with exogenous SP-A for 6 and 18 hr and studying its effects on the AM proteome. RESULTS: We found: 1) less variance between KO males and females than between the WT counterparts by principal component analysis, indicating that SP-A plays a role in sex differences; 2) fewer changes in females when the total numbers of significantly changing protein spots or identified whole proteins in WT or 18 hr SP-A-treated males or females were compared to their respective KO groups; 3) more proteins with functions related to chaperones or protease balance and Nrf2-regulated proteins changed in response to SP-A in females than in males; and 4) the overall pattern of SP-A induced changes in actin-related proteins were similar in both sexes, although males had more significant changes. CONCLUSIONS: Although there seems to be an interaction between sex and the effect of SP-A, it is unclear what the responsible mechanisms are. However, we found that several of the proteins that were expressed at significantly higher levels in females than in males in WT and/or in KO mice are known to interact with the estrogen receptor and may thus play a role in the SP-A/sex interaction. These include major vault protein, chaperonin subunit 2 (beta) (CCT2), and Rho GDP alpha dissociation inhibitor. We conclude that sex differences exist in the proteome of AM derived from male and female mice and that SP-A contributes to these sex differences.